2008
DOI: 10.1177/1094670508324678
|View full text |Cite
|
Sign up to set email alerts
|

How Relationship Age Moderates Loyalty Formation

Abstract: In this article, the authors focus on the concept of relational equity, that is, the customer perception of distributive justice within a continuous customer-provider relationship. The authors investigate the influences of relational equity on attitudinal loyalty and behavioral loyalty. Moreover, they test the hypothesis that relationship age moderates the impact of relational equity on loyalty, adopting a cross-sectional design and data from a sample of Italian customers of mobile phone services ( N = 461). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(22 citation statements)
references
References 73 publications
(121 reference statements)
0
16
0
Order By: Relevance
“…Previous studies have found that perceived service fairness influences behavioral intentions directly (see for example Karatepe, 2006;Namkung & Jang, 2010;Raimondo et al, 2008). Other research findings have indicated that in service recovery situations, consumption emotions partially mediate the relationship between service fairness and repurchase intentions (Chebat & Slusarczyk, 2005;Schoefer & Diamantopoulos, 2008).…”
Section: Conclusion and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have found that perceived service fairness influences behavioral intentions directly (see for example Karatepe, 2006;Namkung & Jang, 2010;Raimondo et al, 2008). Other research findings have indicated that in service recovery situations, consumption emotions partially mediate the relationship between service fairness and repurchase intentions (Chebat & Slusarczyk, 2005;Schoefer & Diamantopoulos, 2008).…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…The relationship between perceived fairness and behavioral intentions has received attention in the marketing literature, generally confirming that perceptions of service fairness can influence behavioral intentions directly (see for example Karatepe, 2006;Raimondo, Miceli, & Costabile, 2008). Swan and Mercer (1983) suggest that perceived fairness leads to complaining/complimenting, word-of-mouth, and repurchase/avoidance behaviors.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…Bolton, 1998;Raimondo et al, 2008;. To the best of our knowledge, there are no studies investigating whether the determinants of customer commitment differ between explicit relationship stages in business-to-consumer relationships.…”
Section: Customer Lifecyclementioning
confidence: 93%
“…Researchers suggest that relationship age plays a role in behavioral outcomes (Raimondo et al 2008;Seiders et al 2005;Verhoef et al 2002). People in lengthy relationships would have more opportunities to gather information about one another, more motivation to acquire information, and more motivation to integrate/assimilate that information into coherent representations (Swann and Gill 1997).…”
Section: Effects Of Relationship Age On Loyalty Intentionsmentioning
confidence: 98%
“…Prior research has suggested that relationship age may have an impact on relational outcomes (Bolton 1998;Raimondo, Miceli, and Costabile 2008;Verhoef, Franses, and Hoekstra 2002). This is highly relevant in health-care services, which are characterized by considerable uncertainty.…”
mentioning
confidence: 99%